Ротор синхронного двигателя с постоянными магнитами - Горобец В. Л. Владимир Леонидович; Куминов А. С. Андрей Сергеевич; Верхотуров А. И. Анатолий Иванович; Киселёв А. Д. Александр Дмитриевич; Сипайлов Г. А. Геннадий Антонович
опубл. 07.08.86